EVALUATION OF THE RESULTS OF SURGICAL AND ENDOVASCULAR CORRECTION OF THE DEFECT OF THE INTERAPTERIAL BARRIER USING ECHOCARDIOGRAPHIC EXAMINATION (World Bulletin of Public Health, 2025)
The atrial septal defect is one of the most common congenital heart defects. According to various authors, patients with atrial septal defect constitute 5-15% of TPS patients. An atrial septal defect is a pathological connection between the right and left atria due to disruptions in septal formation of primary and secondary nature. The review summarizes the anatomical and pathophysiological mechanisms, clinical and instrumental signs of the atrial septal defect, modern principles of diagnosis, and interdisciplinary treatment methods for this pathology.
Keywords: atrial septal defect; right atrium; left atrium; heart defect